IMPACT OF CHARGE AND COSMOLOGICAL CONSTANT ON THE GRAVITATIONAL COLLAPSE OF LEMAITRE TOLMAN BONDI SPACETIME IN F(R,T) GRAVITY (Contemporary Journal of Social Science Review, 2026)
The main aim of this paper is to study the Impact of charge on the gravitational collapse of Lemaitre Tolman Bondi (LTB) space time in f(R, T) gravity. We also discuss the role of f(R, T) gravitational collapse as well as electromagnetic field on collapsing bodies. For this purpose, we consider spherically symmetric LTB relativistic body joined with ideal matter distribution along with electromagnetic field in f(R, T) gravity. We explore the exact analytical models of Maxwell f(R, T) field equations with constant Ricci scalar and trace of energy momentum tensor. The dynamics of collapse system is investigated through system energy content, cosmological and black hole horizons in the presence of electromagnetic field. It is concluded that in addition to matter variables and f(R, T) corrections, the charge also affects the time interval between formation of respective horizons and singularities. We also find that f(R, T) corrections as well as electromagnetic field tend to slow down the collapse process.